The centrality of cognition and coping styles in driving aggressive responses. (November 2022) - Sebalo, Ivan; Ireland, Jane L.; Chu, Simon
Abstract: Objective: Despite the presence of theoretical frameworks explaining aggression, they still require refinement in the form of a specification of mechanisms that facilitate such behaviour. Method: Study 1 recruited participants ( N = 31) from the general population ( N = 20) and from a forensic hospital ( N = 11). It was expected that aggression supportive cognitions and stress would be positively associated with aggressive behaviour. An experimental paradigm was used to induce stress and participants were subsequently given the opportunity to aggress. Study 2 was based on self-report questionnaires in community sample ( N = 462). It was expected that aggressive behaviour and traits would be associated with experienced stress, hostile attributions, coping styles, and attitudes to violence. Specifically, that criminal attitudes to violence will mediate the effect of hostile attribution on aggression, while coping styles will mediate the effect of perceived stress. Results: An Implicit Theory "I am the law" was found to be associated with aggression. Furthermore, elevated skin conductance, but not changes in the heart rate, during the stress task was positively associated with aggression, and only among patients. Structural Equation Model confirmed the mediating role of criminal attitudes to violence and of maladaptive coping style for aggressive behaviour. Conclusion: Aggression-supportive cognitions and maladaptive coping style are specific mechanisms through which external demands or subjective perception of a situation can result in aggressive behaviour.